2018
DOI: 10.1002/lary.27207
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus: An unlikely etiologic factor in sinonasal inverted papilloma

Abstract: NA Laryngoscope, 2443-2447, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
2
25
1
2
Order By: Relevance
“…The aetiological factors contributing to the formation of SIP and SOP are still unknown. Previous studies have demonstrated that the human papilloma virus (HPV) detection rate in SIP is quite variable, and that the role of HPV is ambiguous . SOP was reported to harbour no high‐risk HPV or low‐risk HPV .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiological factors contributing to the formation of SIP and SOP are still unknown. Previous studies have demonstrated that the human papilloma virus (HPV) detection rate in SIP is quite variable, and that the role of HPV is ambiguous . SOP was reported to harbour no high‐risk HPV or low‐risk HPV .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the human papilloma virus (HPV) detection rate in SIP is quite variable, and that the role of HPV is ambiguous. 14,15 SOP was reported to harbour no high-risk HPV or low-risk HPV. 16 Recently, knowledge on the genetic alterations involved in SIP and SOP has increased.…”
Section: Discussionmentioning
confidence: 99%
“…reported that sinonasal IP progression to SCC was significantly associated with the presence of human papillomavirus (HPV) infection (14,15). However, Mohajeri et al compared HPV positivity among sinonasal IP samples and those from patients with SCC by immunohistochemistry and found that HPV was not supported as an etiological driver of IP development or progression to SCC (16). Thus, further research is required to confirm the association between HPV infection and SCC with IP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite absence of HPV in our tonsillar specimens, p16 was present in the epithelium in all cases and in the lymphoid tissue in 92.5% of cases. However, intensity and number of positive cells were generally low when comparing to inverted sinonasal papilloma and oropharyngeal cancer . These low numbers of p16 seen probably resemble normal p16 expression in a regulated cell cycle, where p16 functions according to design.…”
Section: Discussionmentioning
confidence: 98%